Pseudosperma calciphilum (Inocybaceae), a new Mediterranean species from Sardinia (Italy), Malta, and Valencia (Spain) - Sanna, Massimo; Mua, Alberto; Porcu, Giuseppe; Casula, Marco; Rinaldi, Andrea C.; Mifsud, Stephen; Garrido-Benavent, Isaac (Phytotaxa, 2024)
A complete description is provided for Pseudosperma calciphilum (Inocybaceae, Agaricales), a new basidiomycete species from Sardinia (Italy), Malta, and Valencia (Spain) in Europe, along with colour photographs of its macro- and microscopic characters and a comparative study of the similarities and differences from its closest allies. The new species occurs on calcareous soils in Mediterranean habitats preferably under Quercus ilex subsp. ilex and Q. ilex subsp. rotundifolia. Pseudosperma conviviale resembles P. calciphilum in some macro- and microscopic features, but the latter is distinguished by having white velar remnants on pileus, larger spores and by its ecology, as it apparently grows exclusively on calcareous soils. The phylogenetic analyses based on nrITS and nrLSU nucleotide sequence data confirmed that the new species is a member of the former Inocybe section Rimosae sensu stricto, whose species are currently placed in the genus Pseudosperma. The closest relatives are P. melleum, P. conviviale, P. melliolens and P. umbrinellum, from which the new Mediterranean species is well distinguished both morphologically and genetically.